Microenvironment of diabetic foot ulcers: Implications for healing and therapeutic strategies - Jixue Wang; Xirui Yang; Tao Zhou; Haitao Ma; Xingxing Yuan; Shuxun Yan; Siqi Wang (Journal of Research in Medical Sciences)
Diabetic foot ulcers (DFUs) are a common yet serious complication in individuals with diabetes, often presenting as chronic, nonhealing wounds that significantly impair quality of life. The healing process of DFUs is largely influenced by the local microenvironment, which encompasses factors such as hypoxia, inflammation, and the involvement of various cell types. Poor blood circulation in the affected area results in hypoxia, compromising cellular function and restricting nutrient supply, thereby delaying wound healing. In addition, chronic inflammation disrupts immune system balance, with excessive pro-inflammatory cytokines not only failing to facilitate tissue repair but also exacerbating tissue damage. Moreover, key cell types, including fibroblasts, keratinocytes, and macrophages, play crucial roles at different stages of the healing process, contributing to collagen production and skin regeneration. A comprehensive understanding of the complex dynamics within the DFU microenvironment is essential for developing more precise therapeutic approaches, such as advanced drug delivery systems and bioactive materials, aimed at promoting wound healing and reducing the risk of recurrence.